In the Shadow of Djoser's Pyramid Research of Polish Archaeologists in Saqqara - Mysliwiec, Karol Jan (Studies in Classical Literature and Culture, 2020)
The book presents the discoveries made by the Polish archaeological mission in Saqqara, the central part of the largest ancient Egyptian royal necropolis. The area adjacent to the Pyramid of King Djoser on the monument's west side, so far neglected by archaeologists, turned out to be an important burial place of the Egyptian nobility from two periods of Pharaonic history: the Old Kingdom (the late third millennium BC) and the Ptolemaic Period (the late first millennium BC). The earlier, lower cemetery yielded rock-hewn tombs with splendid wall decoration in relief and painting. The book also describes methods of conservation applied to the discovered artefacts and episodes from the mission's life.